Enhancing the fuel properties of rubberwood biomass by moving bed torrefaction process for further applications. (June 2021) - Kongto, Pumin; Palamanit, Arkom; Chaiprapat, Sumate; Tippayawong, Nakorn
Abstract: Rubberwood biomass is widely available in the southern region of Thailand and it has high potential for biofuel applications. Applications of this biomass still have some limitations, however, such as low energy properties and high biological decomposition. Therefore, the aim of this study was to enhance the fuel properties of rubberwood biomass by a torrefaction process. Rubberwood sawdust (RWS) was torrefied at different temperatures (200, 250, and 300 °C) and for various times (20, 40, and 60 min) in a moving bed reactor. The product yield and characteristics of torrefied RWS were investigated. Results showed that the solid yield of torrefied RWS was in the range of 39.07–88.69%, depending on temperature and time. The fuel atomic ratios of torrefied RWS were better than of raw RWS. The energy content and energy density of torrefied RWS were clearly enhanced (19.78–27.17 MJ/kg and 4.94–6.59 GJ/m 3 ). ICP-OES results revealed a variation of inorganic elements in torrefied RWS, which was consistent with the ash components given by XRF. Ash fusion temperature of raw RWS and torrefied RWS ashes was stable at 1458 °C. The slagging index of torrefied RWS was decreased, while its fouling index was elevated. Graphical abstract: Image 1 Highlights: Yield and properties of torrefied RWS were clearly influenced by temperature. Fuel atomic ratios and energy properties of RWS were improved by torrefaction. Fusion temperature of torrefied RWS ash was above 1458 °C. Torrefaction increased fouling index of RWS but reduced its slagging index.